Re-imagining our careers in post-apartheid public psychology: A collaborative autoethnography - Pillay, Suntosh R; Naidu, Thirusha; Geils, Catherine (PINS-Psychology in Society, 2018)
This article is the product of many conversations, debates and reflections amongst three colleagues, as we contemplated our careers as clinical psychologists in the public service in South Africa. Having trained at roughly five year intervals since 1995, our paths intersected in 2013 when we found ourselves working together in a public hospital in KwaZulu-Natal. Using a collaborative autoethnographic approach, we interrogate the politics of post-apartheid psychology training and practice. We engaged in three cycles of personal, critical and collaborative reflective strategies. Our shared insights suggest that our careers are meaning-making journeys of anger at, but inspiration from, the public health care system. Inhabiting the roles of psychotherapist, activist, and philosopher, our methodological intention is to lose objective dispassion and use radical subjectivity, both in form and content of this article. We unearth, probe and question our personal, often unspoken, thoughts about our professional identities and argue that psychology in South Africa is not doing justice to the historical injustices it ought to be helping alleviate. We hope that this article inspires and emboldens psychologists to use the transformative power of their own voice to write the personal into the political, as a necessary disruption to current academia.